User Acceptance of Gold Pawn Application in Syariah Bank: Penerimaan Pengguna Terhadap Aplikasi Gadai Emas di Bank Syariah - Anggraeni, Indah Kurnia; Krisnaningsih , Diah (Indonesian Journal of Islamic Studies, 2025)
General Background: The integration of information technology (IT) in Islamic banking has transformed operational processes, particularly in financing services such as gold pawning. Specific Background: Bank Syariah X implemented the E-Steem application to streamline assessment, analysis, and disbursement processes in gold pawns while ensuring compliance with Sharia principles. Knowledge Gap: Despite technological adoption, limited research has explored how user perceptions and acceptance affect system utilization in Islamic pawn financing. Aims: This study investigates user acceptance of the E-Steem application using the UTAUT model, focusing on performance expectancy, effort expectancy, social influence, and facilitating conditions. Results: Findings indicate that these four UTAUT factors collectively shape user acceptance, accelerating pawn processes, reducing errors, and enhancing transparency. Novelty: This research uniquely combines qualitative descriptive methods with UTAUT analysis in a Sharia-compliant pawn context. Implications: Understanding user acceptance provides guidance for optimizing IT systems in Islamic financial services, promoting operational efficiency and regulatory compliance. Highlights: Four UTAUT variables shape user adoption in Sharia-compliant pawns. E-Steem accelerates pawn processes and reduces operational errors. Findings guide IT optimization in Islamic financial services. Keywords: Gold Pawn; UTAUT; Islamic Banking; Technology Adoption; User Acceptance